A comparative reading on the level of job satisfaction of Venezuelan teachers between 1996 y 2018 - Ramírez, Tulio; Torres Cruz, Dóris Lilia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The research aims at comparing the levels of job satisfaction of a sample of Venezuelan official teachers of Primary and High School during the years of 1996 and 2006. Originality: High levels of job dissatisfaction were evidenced in the 7 factors that load the scale applied. Comparing these results with those achieved in 1996 and 2006, there was a deepening of the state of dissatisfaction which particularly had already been perceived since 24 years ago in extrinsic factors to work such as remuneration, the job environment and its conditions, as well as with profits. Method: a mixed approach research has been considered, with which the strategy of the job satisfaction scale is used, managed in online way and built from the Bifactorial Theory elaborated by Herzberg, Mausner and Snyderman in 1959. The conclusion highlights that the intrinsic or motivating factors that have to do with the nature of the work itself (recognition of work, professional autonomy and work in itself) present satisfaction levels as well as those found in the previous studies referred to.